Infectious Bronchitis Virus (Gammacoronavirus) in Poultry Farming: Vaccination, Immune Response and Measures for Mitigation - Md. Safiul Alam Bhuiyan; Zarina Amin; Kenneth Francis Rodrigues; Suryani Saallah; Subir Sarker; Shafiquzzaman Siddiquee; Sharifudin Md Shaarani (MDPI, 2024)
Indexed by WOS/SCOPUS/ERA